UPAYA PENINGKATAN PEMAHAMAN BULLYING PADA TEMAN SEBAYA MELALUI LAYANAN BIMBINGAN KELOMPOK SISWA KELAS X SMK - Marfuatun, Marfuatun; Suma’yah, Suma’yah (JKP (Jurnal Konseling Pendidikan), 2022)
Indonesia is one of the countries that is quite concerned about handling bullying cases as proven to be contained in the law, besides that the smallest prevention is carried out within the scope of schools as stated in the Minister of Education and Culture. Bullying or also known as bullying is an unpleasant act that is done by someone to another person. The findings of the problem were found in one of the schools in East Lombok Regency, precisely at the Kotaraja Vocational High School (SMK), namely students experiencing bullying. One effort that can be done is to provide counseling services while based on the information the service has not been provided optimally. The application of group counseling services can be carried out using many approaches, one of which is the behavior approach so that the purpose of this study is to determine the effectiveness of group counseling services to increase understanding of bullying among peers in class X SMK Kotaraja. The research method used is quantitative with the type of experiment. Based on the results of data analysis using the t-test, it shows that t-count is greater than t-table (3.89> 2.36) at a significant level of 5% indicating that group counseling services are effective in increasing understanding of bullying in class X students of SMK Kotaraja.